Oil Fictions World Literature and Our Contemporary Petrosphere - Balkan, Stacey; Nandi, Swaralipi (Penn State University Press, 2022)
Oil, like other fossil fuels, permeates every aspect of human existence. Yet it has been largely ignored by cultural critics, especially in the context of the Global South. Seeking to make visible not only the pervasiveness of oil in society and culture but also its power, Oil Fictions stages a critical intervention that aligns with the broader goals of the energy humanities.Exploring literature and film about petroleum as a genre of world literature, Oil Fictions focuses on the ubiquity of oil as well as the cultural response to petroleum in postcolonial states. The chapters engage with African, South American, South Asian, Iranian, and transnational petrofictions and cover topics such as the relationship of colonialism to the fossil fuel economy, issues of gender in the Thermocene epoch, and discussions of migration, precarious labor, and the petro-diaspora. This unique exploration includes testimonies of the oil encounter-through memoirs, journals, and interviews-from a diverse geopolitical grid, ranging from the Permian Basin to the Persian Gulf.By engaging with non-Western literary responses to petroleum in a concentrated, sustained way, this pathbreaking book illuminates the transnational dimensions of the discourse on oil. It will appeal to scholars and students working in literature and science studies, energy humanities, ecocriticism, petrocriticism, environmental humanities, and Anthropocene studies.In addition to the editors, the contributors to this volume include Henry Obi Ajumeze, Rebecca Babcock, Ashley Dawson, Sharae Deckard, Scott DeVries, Kristen Figgins, Amitav Ghosh, Corbin Hiday, Helen Kapstein, Micheal Angelo Rumore, Simon Ryle, Sheena Stief, Imre Szeman, Maya Vinai, and Wendy W. Walters.